Member importance prediction and failure response analysis for cable network antennas. (1st September 2022) - Yuan, Pengfei; He, Baiyan; Nie, Rui; Zhang, Lianhong; Yu, Hongbo; Wang, Guobiao; Ma, Xiaofei
Highlights: The impact of individual member failure on the cable network antenna is studied. A sensitivity-based member importance prediction method is proposed. The condition of cable slack is considered in the member importance prediction. A failure response analysis approach is proposed based on the VFIFE method. Abstract: Cable network antennas are likely to experience damage from the extreme space environment. This will deteriorate the antennas' performance and even lead to the scrapping of antennas. To date, effective means for on-orbit maintenance of cable network antennas are lacking. Therefore, it is necessary to investigate the influence of each member failure on the antenna and find the most important ones before launching. But the method of exhaustion to analyze each member failure response is inefficient. Hence, we propose an importance prediction method for finding the key members of the antenna based on the sensitivity analysis. The sensitivity analyses with respect to the failure member are carried out, in which the condition of cable slack caused by member failure is considered. The node displacement sensitivity is used to predict the member importance. After that, based on the vector form intrinsic finite element method, a response analysis method for the incomplete antenna after member failure is proposed. The proposed method can accurately capture the transient response of the antenna and effectively avoid the non-convergence problem caused by slack cables. A numerical example is provided, and the most important members are predicted, which should be given special concern in the design stage.